Monitoramento de pavimento composto por revestimento delgado e base melhorada com cimento - Santos, Hebert Oliveira (2019)
Although the highway system is the most important for Brazilian development, the pavements’ quality is low, with more than 50% of the built road networks presenting problems; one of the responsible for this situation is the design method currently used, that presents limitations. It is necessary to develop researches that allow the implementation of a method that among other factors that takes into account the deformation stresses of the pavement. In this context, this study aims to present the preliminary results of one of the monitored test track in the state of Goiás, GO-230, incorporating mechanistic analysis to contribute to the database of materials, technologies and performance of an asphalt pavement executed with double surface treatment (TSD). For this, laboratory tests were performed with the materials used for the track pavement construction, aiming the characterization, mechanical, and resilient behavior of the components of each layer, The gravel with cement mix behavior in three different grades was also evaluated. TSD grain sizing was checked with theoretical and empirical methods complemented by the calculation of the PUC coefficient. The conditions under the pavement was built, the functional conditions, micro, macrotexture, apparent defects, and the structural behavior were investigated after six months of the traffic opening. The actual traffic was determined, the stresses and deformations developed by the pavement structure were analyzed and the resilient modules obtained by the back-analysis process was obtained by the BAKFAA and BackMedina softwares. Swelling suppression and high mechanical gain were observed with the addition of cement in the gravel. It was found that the Brazilian requirements for TSD execution are generic, differing from the sizing methods and allowing the emulsion to be oversized. Execution control showed failures in the construction process while monitoring shows many apparent pathologies. The stress-strain analysis predicted high deformations in the subbase and subgrade that decreased while the base stiffness was increased. The back-analyzed modules presented higher values than those measured in the laboratory by the two softwares used, and BackMedina offers a more accurate adjustment to the deflection curves. Studies of this work, both in the field and in the laboratory, have shown that the project life of 10 years is unlikely to be achieved.